LncRNA PPP1R14B-AS1 Promotes Tumor Cell Proliferation and Migration via the Enhancement of Mitochondrial Respiration - Yang, Yibin; Zhang, Yuan; Miao, Lihong; Liao, Weijie; Liao, Weifang (Frontiers in Genetics, 2020)
PPP1R14B-AS1 is an antisense long noncoding RNA with unknown functions. Herein, gene differential analyses were performed using the data of patients with liver cancer and lung adenocarcinoma from The Cancer Genome Atlas database. PPP1R14B-AS1 was found to be upregulated and also overexpressed in 10 other types of cancers. In addition, PPP1R14B-AS1 overexpression was associated with poor overall prognosis in eight cancers. Furthermore, PPPAR14B-AS1 upregulation was positively associated with the worsening development of liver and lung adenocarcinoma cancers and related to poor disease-free survival. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses suggested that PPP1R14B-AS1 strongly participated in regulating cell aerobic respiration processes, such as mitochondrial electron respiration chain and NADH dehydrogenation processes. Cell cytoplasmic and nuclear RNA purification assessment results revealed that PPP1R14B-AS existed in the cell nucleus and cytoplasm. The knockdown of PPP1R14B-AS1 in HepG2 and A549 cells using PPP1R14B-AS1-specific siRNAs decreased mitochondrial respiration as demonstrated by the reduction in basal respiration and ATP production. Moreover, PPP1R14B-AS1 downregulation did not obviously affect cell glycolysis ability. Finally, PPP1R14B-AS1 inhibition inhibited HepG2 and A549 cell migration and proliferation. In summary, our study found for the first time that PPP1R14B-AS1 could be a potential biomarker for cancer diagnosis and that PPP1R14B-AS1 inhibition could be a potentially effective therapy.